Towards a Reception History of the Chaldaean Oracles. - Wheeler, Graham John (International Journal of the Classical Tradition, 2021)
The article presents the discussion on Chaldaean Oracles counting as one of the most mysterious and bafing texts coming down from classical antiquity. Topics include collections of oracles compiled by the Platonist intellectuals Porphyry and Cornelius Labeo; Chaldaean Oracles composed in the Greek language using the poetic form of dactylic hexameters; and refection of the importance of fre in the Stoic philosophical and cosmological system.